Analyses of long non-coding RNA and mRNA profiles in the spinal cord of rats using RNA sequencing during the progression of neuropathic pain in an SNI model. Issue 12 (2nd December 2017) - Zhou, Jun; Fan, Youling; Chen, Hongtao
ABSTRACT: The pathogenesis of neuropathic pain (NP) is characterized by an increased responsiveness of nociceptive neurons in the nervous system. However, the molecular mechanisms underpinning the NP still remain elusive. Recent data suggest that long non-coding RNAs (lncRNAs) regulate expression of NP-associated genes. Herein, we analyzed lncRNAs and mRNA profiles in the spinal cord of rats by RNA sequencing during the progression of NP in a spared nerve injury (SNI) model. Sprague-Dawley (SD) rats were employed for the establishment of the SNI models, and nociceptive responses to mechanical and thermal stimuli were measured 3 hours prior to surgery and on postoperative days 1, 3, 7 and 14, with L4-5 spinal cords extracted from three SD rats under deep anesthesia at each time point after behavioral test. SNI rats exhibited higher sensitivity to mechanical stimuli from days 1 to 14. Mechanical hyperalgesia reached a steady peak at day14 after surgery, whereas thermal allodynia did not develop. The results of second-generation sequencing suggested that the expression profiles of lncRNAs and mRNAs were significantly altered in spinal cords of SNI rats versus the control rats at different stages during NP. Differentially expressed (DE) lncRNAs and mRNAs were demonstrated at each stage during the NP course using Volcano Plot, Venn and Hcluster heatmap analyses. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) biological pathway analyses were performed to predict the functionalities of differentially expressed lncRNAs and target genes. Protein interaction networks were constructed based on the correlation analyses of DE lncRNA target proteins at 7 and 14 days after SNI, respectively. Taken together, our results revealed the profiles of lncRNAs and mRNAs in the rat spinal cord under an NP condition. These lncRNAs and mRNAs may represent new therapeutic targets for the treatment of NP.